English Morphology - Damatius Wagiman Adisutrisno (Widya Mandala Surabaya Catholic University, 2013)
There is a popular understanding among English learners that meaning lies in words. This is only partially true. In English monomorphemic words meaning lies in the single morphemes which are also the words. However, there are a lot of bimorphemic or polymorphemic words in English. The meaning of these words is determined by the units of meaning that combine into words. These units of meaning are called morphemes. Meaning lies in morphemes. In English the meaning of words lies in free morphemes, bound stems, prefixes, suffixes, and superfixes